Implementation of Kahoot as a Digital Assessment Tool in English Formative Test for Students of SMP Negeri 2 Temanggung in the Academic Year of 2019/2020 - Sofyana, Andi Widdaya; Faridi, Abdurrachman; Shakiyya, Zulfa (Universitas Negeri Semarang, 2020)
The paper aims to investigate the applicability of the Kahoot as a digital assessment tool. The participants of this study were 32 students of 8G at SMP Negeri Temanggung in the academic year 2019/2020. Kahoot was implemented in English formative test. This is a mixed method with survey technique to collect data and qualitative descriptive analysis to analyze the data. The results of the study indicated that the students thought that Kahoot was enjoyable, informative, useful, and fine. Those were analyzed in descriptive qualitative method. The finding reveals five results: Students good perception on using Kahoot in their English formative test. They can actively participate on the test and get the result directly from the teacher after all the students finished the test. The validity, reliability, and practicality of the test can be seen from the content that has been designed by the researcher, the practical usage of the application is also become the important aspect to be analyzed. Due to COVID -19 the students and teacher cannot do the test in the classroom setting whereas they do the test at home, the effectiveness of using this application compare to paper based is more effective that paper based. The students can enjoy doing the test at home and they didn’t need to come to school. The implications are not only good for teacher and students, but also for the school, stake holder that is really helped by the existence of the application during distance learning.Keywords: Kahoot, Digital assessment tool, and English formative test.